Electroreduction of graphene oxide on titanium at constant potential - Chen, Wei (2015)
Titanium and its alloys are extensively used in biomedical application, such as load bearing bone, hip joint replacement and bone splints due to its outstanding biocompability, corrosion resistance and high strength. It has been reported that titanium could be modified with graphene to enhance the tensile strength and durability, as well as reduction of weight. Commercially, chemical vapour deposition (CVD) is used to produce high-purity and high performance graphene. However, this method is very costly and the complication in the parameters controlled. Hence, graphene oxide (GO) is chosen as the alternative for the preparation of graphene like materials[1], which is inexpensive with large-scale production. Graphene oxide (GO) was reduced to reduced graphene oxide (rGO) through constant potential electroreduction. Several cathodes and electrolytes were compared to optimize the reduction of the GO. At the same time, the rGO was electrodeposited on titanium (Ti) coated silicon (Si) wafer. The coverage, surface morphology and elements of rGO coated samples and the effectiveness of the reduction were evaluated by optical microscopy, Field emission scanning electron microscopy (FESEM), Energy-Dispersive X-Ray Spectroscopy (EDS) and Raman spectroscopy, respectively. The ideal conditions of reduction were evaluated and the optimum conditions for synthesizing graphene on the Ti coated Si substrate were defined via heuristics approach after characterization.